2008
DOI: 10.1186/1477-7819-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Invasive micropapillary carcinomas arising 42 years after augmentation mammoplasty: A case report and literature review

Abstract: Background: There has been no definitive consensus regarding the causal relationships between foreign bodies in the breast and carcinogenesis. This report describes the first case of invasive micropapillary carcinomas after augmentation mammoplasty. Multiple tumors located in immediate contact with the siliconomas suggested a causal link between the siliconomas and carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Histologically, inflammatory granulomas and foreign body giant cells were observed with stromal invasion of invasive ductal carcinoma. Various histological types of cancer have been reported after liquid silicone injection in the previous literature [ 6 , 12 , 15 , 17 , 18 , 20 - 23 ]. Interestingly, there are two cases of squamous cell carcinoma following liquid silicone injection [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, inflammatory granulomas and foreign body giant cells were observed with stromal invasion of invasive ductal carcinoma. Various histological types of cancer have been reported after liquid silicone injection in the previous literature [ 6 , 12 , 15 , 17 , 18 , 20 - 23 ]. Interestingly, there are two cases of squamous cell carcinoma following liquid silicone injection [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The National Institutes of Health found no associations between breast implants and cancer, autoimmune disorder, neurologic disorder, or other systemic diseases. 63 Moreover, the risk of breast cancer is not higher for silicone implants compared with saline-filled implants. 63,64 However, there have been a few reports of carcinoma which seemed to arise from the breast implant capsule.…”
Section: Carcinoma In the Capsule Or Adjacent To The Capsulementioning
confidence: 99%
“…Some authors report in singular cases that cancers in augmented women usually are more advanced at the time of detection (13,14), whereas others have reported no significant difference in tumor size or stage at the time of diagnosis in augmented women compared to non-augmented women.…”
Section: Breast Cancer Characteristics Between Women Treated With Primentioning
confidence: 99%
“…Tanaka et al reported in 2008 a case of three invasive micropapillary carcinomas in a 64-year-old woman who underwent breast augmentation 42 years before (14). The multiple tumors were located next to the siliconomas suggesting a possible relationship between siliconomas and the onset of carcinomas.…”
Section: Breast Cancer Characteristics Between Women Treated With Primentioning
confidence: 99%
See 1 more Smart Citation